Aging Stereotypes Must be Taken Into Account for the Diagnosis of Prodromal and Early Alzheimer Disease. (January 2016) - Régner, Isabelle; Mazerolle, Marie; Alescio-Lautier, Béatrice; Clarys, David; Michel, Bernard; Paccalin, Marc; Piolino, Pascale; Rigalleau, François; Sambuchi, Nathalie; Huguet, Pascal
Abstract : Because of a dramatic increase of older people worldwide, screening for prodromal state of Alzheimer disease (AD) is a major societal challenge. Many individuals diagnosed with prodromal AD, do not convert to AD, some remaining stable and others reversing back to normal. We argue that an important source of this overdiagnosis comes from negative aging stereotypes (eg, the culturally shared beliefs that aging inescapably causes severe cognitive decline and diseases). Many laboratory studies show that such stereotypes impair memory performance in healthy older adults, producing inflated age differences. Research is needed to examine how aging stereotypes implicitly permeate neuropsychological testing and contribute to false positives.